Superconductivity and non-Fermi-liquid behavior of La3Pd4Si4 and Ce3Pd4Si4 - Kneidinger, F. (2013)
Fil: Sereni, J. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina